The impact of overhead sports: assessment of shoulder range of motion in 1st league professional volleyball players - Almeida, J.; Martins, M. J.; Sá, M.; Ribeiro, B.; Almeida, M. J.; Torres, J. (British Journal of Sports Medicine, 2021)
Background: Throwing is a highly skilled movement performed at the extremes of glenohumeral motion.The constant microtrauma in the throwing shoulder challenges the physiologic limits of the surrounding tissues and leads to modifications in range of motion, due to osseous and soft tissue adaptations. Objective: We aimed to characterize the changes that occur in glenohumeral mobility in volleyball players, determining if these would be different compared to other overhead sports and if differences existed between the two shoulders. Design: This was a cross-sectional study, with clinical data collected from questionnaires and functional evaluation using a goniometer. Setting: The subject group consisted of volleyball players from the major league and/or the national team. Participants: The selection criterion was being a volleyball masculine athlete of a major competition without shoulder complaints; this enrolled a total of 66 professional males. Interventions Bilateral range of motion (active and passive) was assessed with a goniometer, in both throwing and nonthrowing shoulder. We also tested stability. Main Outcome Measurements: We measure forward elevation, extension, external and internal rotation. The specific tests were apprehension, anterior and posterior drawer, and the sulcus sign. Results: The dominant shoulder displayed significantly increased external rotation when compared with the non-dominant (120.92°±14.85 vs 106,78°±12,53). Internal rotation was decreased by 11,99° in the throwing shoulder (p=0.047). Concerning forward elevation, a tendency for greater values was noted (p=0.08), with a higher degree in the throwing arm. Conclusions: Range of motion was different between shoulders. Our athletes had an increase in external rotation and a loss of internal rotation in the throwing shoulder, being concordant with what is described in other overhead sports. Furthermore, the dominant shoulder had a significant increase in forward elevation. These findings support the need of performing these evaluations to monitor the development of injuries, so that preventive measures can be taken.